2003
DOI: 10.1002/chin.200318216
|View full text |Cite
|
Sign up to set email alerts
|

New Quinone Sulfates from the Crinoids Tropiometra afra macrodiscus and Oxycomanthus japonicus

Abstract: New Quinone Sulfates from the Crinoids Tropiometra afra macrodiscus and Oxycomanthus japonicus -[isolation, structure elucidation and antifeedant activity]. -(TAKAHASHI, D.; MAOKA*, T.; TSUSHIMA, M.; FUJITANI, K.; KOZUKA, M.; MATSUNO, T.; SHINGU, T.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Both 1 and 2 were also found in extracts from the crinoids Heterometra savi, Lamprometra kluzingeri (Erdman and Thomson 1972), and Oxycomanthus japonicus (Takahashi et al 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Both 1 and 2 were also found in extracts from the crinoids Heterometra savi, Lamprometra kluzingeri (Erdman and Thomson 1972), and Oxycomanthus japonicus (Takahashi et al 2002).…”
Section: Discussionmentioning
confidence: 93%
“…However, secondary metabolites such as quinones may also play a role in chemical defense. Hypericin and gymnochromes are well known for their biological activity (8,24), and antifeedant activities against fish have been reported for structurally related anthraquinone pigments from comatulids (27,28). Previous observations on two extant isocrinids, Endoxocrinus parrae and Neocrinus decorus, suggested that stalked crinoids lack chemical defense against fish predation, supporting the hypothesis that restriction of stalked crinoids to deep-water habitats may have resulted from the Mesozoic radiation of durophagous fishes in shallow seas (29).…”
Section: Resultsmentioning
confidence: 77%
“…Hypericin‐like compounds (Fig. 1) occur in diverse taxa and include stentorin, the blepharismins and maristentorin in heterotrich ciliates (6–10), fringelites in fossil crinoids (11), brominated gymnochromes in modern crinoids (11–14) and fagopyrin in Fagopyrum (buckwheat) (5). Among the more striking aspects of hypericin and the hypericin‐like pigments are their absorption and emission spectra.…”
Section: Introductionmentioning
confidence: 99%